Assessing China's impact on poverty in the Greater Mekong subregion (Institute of Southeast Asian Studies, 2013)
Since the dawn of the industrial revolution, and the ushering in of an era of global economic relations, the United States and Europe have been the core poles of economic power. However, China along with India is increasingly challenging the traditional economic hegemony. An issue of great importance is how this shift in the global economic balance of power will affect developing economies and the transition economies of the Greater Mekong Subregion (GMS), which are located in China's backyard and deeply integrated into its economy through regional supply chains.
Keywords: Economic development -- Mekong River Region; Economic development -- Southeast Asia